Enhanced Re-Endothelialization of Decellularized Rat Lungs - Stabler, Collin T. (Tissue Eng Part C Methods, 2016)
Decellularized lung tissue has been recognized as a potential platform to engineer whole lung organs suitable for transplantation or for modeling a variety of lung diseases. However, many technical hurdles remain before this potential may be fully realized. Inability to efficiently re-endothelialize the pulmonary vasculature with a functional endothelium appears to be the primary cause of failure of recellularized lung scaffolds in early transplant studies. Here, we present an optimized approach for enhanced re-endothelialization of decellularized rodent lung scaffolds with rat lung microvascular endothelial cells (ECs). This was achieved by adjusting the posture of the lung to a supine position during cell seeding through the pulmonary artery. The supine position allowed for significantly more homogeneous seeding and better cell retention in the apex regions of all lobes than the traditional upright position, especially in the right upper and left lobes. Additionally, the supine position allowed for greater cell retention within large diameter vessels (proximal 100–5000 μm) than the upright position, with little to no difference in the small diameter distal vessels. EC adhesion in the proximal regions of the pulmonary vasculature in the decellularized lung was dependent on the binding of EC integrins, specifically α1β1, α2β1, and α5β1 integrins to, respectively, collagen type-I, type-IV, and fibronectin in the residual extracellular matrix. Following in vitro maturation of the seeded constructs under perfusion culture, the seeded ECs spread along the vascular wall, leading to a partial reestablishment of endothelial barrier function as inferred from a custom-designed leakage assay. Our results suggest that attention to cellular distribution within the whole organ is of paramount importance for restoring proper vascular function.